Effect of hydrogen peroxide on persistent sodium current in guinea pig ventricular myocytes - Ma Ji-hua; Luo An-tao; Zhang Pei-hua (Acta Pharmacologica Sinica, 2016)
Aim: To study the effect of hydrogen peroxide (H2O2) on persistent sodium current (INa.P) in guinea pig ventricular myocytes. Methods: The whole-cell, cell-attached, and inside-out patch-clamp techniques were applied on isolated ventricular myocytes from guinea pig. Results: H2O2 (0.1 mmol/L, 0.5 mmol/L and 1.0 mmol/L) increased the amplitude of whole-cell INa.P in a concentration-dependent manner, and glutathione (GSH 1 mmol/L) reversed the increased INa.P H2O2 (1 mmol/L) increased persistent sodium channel activity in cell-attached and inside out patches. The mean open probability was increased from control values of 0.015plusminus0.004 and 0.012plusminus0.003 to 0.106plusminus0.011 and 0.136plusminus0.010, respectively (P